Performance Allowance, Organizational Culture, Work Pressure, and Leadership Towards Fraudulent Behavior - Daryanto, Daryanto; Pawenang, Supawi; Sarsono, Sarsono (Indonesian Journal of Islamic Economics and Finance, 2024)
This study aims to determine the effect of performance allowances, organizational culture, work pressure, and leadership on fraud. This research was carried out by the KPP Madya Surakarta organization. Over the course of seven months, beginning in January 2024 and ending in July 2024, the study was conducted there. The reason why the researcher determined that the best time to do the investigation was between January and July of 2024. All of the personnel of KPP Madya Surakarta, which amounted to 116 individuals, were included in this study's data collection. The method of sampling that was utilized in this investigation was known as purposive sampling. 58 employees from KPP Madya Surakarta were used as samples for this study. These personnel included all Account Representatives and examiners. When examining the impact of many independent variables on a dependent variable, multiple linear regression analysis was utilized as the method of study. Specifically, to ascertain the degree to which performance allowances, corporate culture, job pressure, and leadership are all closely related to the phenomenon of fraud. Despite the fact that leadership does not have a substantial impact on fraud, the findings of this study indicate that performance allowances, organizational culture, and work pressure all have a favorable and significant impact on the phenomenon of fraud.